The Mexican Consortium of Epidemiological Studies for the Prevention, Diagnosis, and Treatment of Chronic Kidney Disease: a review of collaborating studies - Adrian Cortés-Valencia; Saraí Ortiz-Rodríguez; Nydia Balderas-Arteaga; Andrés Catzin-Kuhlmann; Ricardo Correa-Rotter; Clicerio González-Villalpando; Aida Jiménez-Corona; Ruy López-Ridaura; Miguel Mejia; Jorge Salmerón; Juan Tamayo; Martín Lajous; et al. (Instituto Nacional de Salud Pública, 2022)
Objective. To harmonize participants' information from five epidemiological studies. Materials and methods. The Mexican Consortium of Epidemiological Studies for the Prevention, Diagnosis, and Treatment of Chronic Kidney Disease (RenMex, by its Spanish acronym) was established in 2018. RenMex is a consortium of five studies: The Mexican Teachers Cohort Study; the Mexico City Diabetes Study; the Health Workers Cohort Study; the Comitán Study; and the Salt Consumption in Mexico Study, which assessed baseline serum creatinine, albumin, and C-reactive protein, all performed with standardized techniques. Results. RenMex includes 3 133 participants, with a mean age of 44.8 years, 68.8% women, 10.8% with a previous medical diagnosis of type 2 diabetes, and 24.1% living with obesity. Conclusions. In the future, RenMex will work on more detailed analyses with each cohort allowed to opt in or out for each topic according to their individual data.